National Medical Expenditure Survey, 1987: Household Survey, Hospital Stays Data (Public Use Tape 14.4) ([Verlag nicht ermittelbar], 1993)
The Household Survey is one of the three major components of the 1987 National Medical Expenditure Survey (NMES). (The other two components are the Survey of American Indians and Alaska Natives [SAIAN] and the Institutional Population Component.) Like its predecessors, the 1987 NMES provides information on health expenditures by or on behalf of families and individuals, the financing of these expenditures, and each person's use of services. The Household Survey was fielded over four rounds of personal and telephone interviews at four-month intervals. Baseline data on household composition, employment, and insurance characteristics were updated each quarter, and information on all uses of and expenditures for health care services and sources of payment was obtained. The data on Public Use Tape 14.4 provide information on hospital stays, the major reason reported by household respondents for admission and related conditions, length of stay, medical procedures performed, cost of services, and means of payment. These data were collected in the four rounds of interviews and in the NMES Medical Provider Survey, a survey designed to reduce the potential bias in medical expenditure estimates derived solely from data provided by household respondents. The data file contains one record per hospital stay for each eligible person in the Household Survey who reported at least one stay during 1987.